1999
DOI: 10.1063/1.370182
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of local dielectric breakdown in ultrathin SiO2 films using scanning tunneling microscopy and spectroscopy

Abstract: Local dielectric breakdown of ultrathin SiO 2 films grown on silicon substrates has been investigated by using scanning tunneling microscopy ͑STM͒ and scanning tunneling spectroscopy ͑STS͒. We found that STM observation can reveal individual quasibreakdown spots created by hot-electron injection into the oxide, as well as features of the topography such as atomic steps on the oxide surface. STS was used to study the local electrical properties of the oxide films before and after electrical stressing. We observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…19 Each point represents data averaged from more than 5 measurements of the same flake. The EBD obtained in this study is in agreement with that reported previously for thin BN.…”
mentioning
confidence: 99%
“…19 Each point represents data averaged from more than 5 measurements of the same flake. The EBD obtained in this study is in agreement with that reported previously for thin BN.…”
mentioning
confidence: 99%
“…5 Recently, the use of scanned probes to perform local electrical measurements on thin SiO 2 films has provided an opportunity for studying the underlying breakdown mechanisms, which operate at the nanoscale. 6 Conductive-atomic force microscopy ͑CAFM͒ has been employed to examine local variations in Fowler-Nordheim tunneling due to variations in oxide thickness. 7 Scanning tunneling microscopy has been used to generate, and subsequently image, isolated stress induced quasibreakdown sites, 6 and CAFM employed further to observe local current fluctuations attributed to charging of stress-induced defect sites.…”
mentioning
confidence: 99%
“…6 Conductive-atomic force microscopy ͑CAFM͒ has been employed to examine local variations in Fowler-Nordheim tunneling due to variations in oxide thickness. 7 Scanning tunneling microscopy has been used to generate, and subsequently image, isolated stress induced quasibreakdown sites, 6 and CAFM employed further to observe local current fluctuations attributed to charging of stress-induced defect sites. 8 In this letter we make use of CAFM to study the nanoscale spatial distribution of quasibreakdown in native SiO 2 films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Watanabe et al 16 have investigated the local dielectric breakdown of ultrathin SiO 2 films by STM/STS and observed quasibreakdown spots on the surface as a result of the change of conductance due to the hot electron injection at high bias voltage of 10 V. Although in our case a considerably smaller bias voltage of 100 mV was applied to the sample during topography imaging, a local breakdown might still occur due to the stronger electric field that may exist at the top of the nanocolumn. However, an electrical breakdown should lead to observable surface topographical change, which was not detected in our scans.…”
mentioning
confidence: 99%